La comunicación científica oral de los estudiantes de Medicina Veterinaria y Zootecnia de la Universidad Central “Marta Abreu” de Las Villas - Méndez Lloret, Darlén; Rodríguez González, Dalila; Alonso Paz, Silvia; Navarrete Reyes, María del Carmen (My University, 2016)
Actually, the development of the scientific communication is a main element for all university students, the dynamics of the company needs to communicate the research findings with coherence and cohesion. The aim of this article is to socialize the experience of how promoting the oral scientific communication in the faculty of Veterinary Medicine of the Central University “Marta Abreu” of Las Villas. In the past, the observation and bibliographical review were used as empirical methodActually, the development of the scientific communication is a main element for all university students, the dynamics of the company needs to communicate the research findings with coherence and cohesion. The aim of this article is to socialize the experience of how promoting the oral scientific communication in the faculty of Veterinary Medicine of the Central University “Marta Abreu” of Las Villas. In the past, the observation and bibliographical review were used as empirical methodActually, the development of the scientific communication is a main element for all university students, the dynamics of the company needs to communicate the research findings with coherence and cohesion. The aim of this article is to socialize the experience of how promoting the oral scientific communication in the faculty of Veterinary Medicine of the Central University “Marta Abreu” of Las Villas. In the past, the observation and bibliographical review were used as empirical method. One experiment was done with the first and four year students who belong to this faculty from this university, as a result the students lacks oral scientific communication. To mitigate the detected issues were made and implemented by didactic actions that wwere improved this kind of communication in the sample students. Nowadays, the students have a good perception of the social and culturalimportance that scientist performs in the oral scientific communication.

El desarrollo de la comunicación científica es un elemento básico para todos los estudiantes universitarios en la actualidad, pues la dinámica de la sociedad requiere comunicar con coherencia y cohesión los resultados de la investigación. El objetivo del artículo es socializar la experiencia de cómo potenciar la comunicación científica oral en los estudiantes de Medicina Veterinaria y Zootecnia de la Universidad Central “Marta Abreu” de Las Villas. Para el desarrollo del trabajo se utilizaron métodos del nivel empírico como la observación y la revisión bibliográfica. Se realizó una prueba pedagógica de entrada a los estudiantes de primer y cuarto años que cursaban la carrera de Medicina Veterinaria y Zootecnia en dicha universidad, en el curso académico 2013-2014; esta evidenció carencias en la comunicación científica oral de los estudiantes. Para erradicar los problemas detectados se elaboraron e implementaron acciones didácticas que perfecciionaran este tipo de comunicación en los estudiantes muestreados. Actualmente los estudiantes valoran de manera positiva la importancia social y cultural que tiene en la actividad científico-investigativa la comuni cación científica oral.
The oral scientificcommunication students of Veterinary Medicine of the Central University ¨Marta Abreu¨of Las Villas
Keywords: Comunicación; Estudiante Universitario; Medicina Veterinaria; Communication; University Students; Veterinary Medicine; Universidad Central ¨Marta Abreu¨de Las Villas; Comunicación Científica